Sosialisasi Nilai-Nilai Keselamatan Jalan Raya Di SMKN 2 Kota Makassar - Noor Fadilah Romadhani; Moeh. Kay Muddin Asnur; Muhammad Haristo Rahman; Iriandy; Hartini Ramli (Vokatek: Jurnal Pengabdian Masyarakat, 2023)
Traffic accidents is a major issue in the aspect of road safety. Based on data from the Directorate General of Road Transportation of the Ministry of Transportation in 2020 that 70% of traffic accident victims come from high school level students. The high number of traffic accident among students means that there is still a lack of awareness of the importance of road safety. This Community Service Activity is in the form of socialization with the theme "Road Safety Values in Vocational School Students in Makassar City". This activity aims to increase awareness and instill road safety cultural values. The implementation of this activity is carried out by conducting initial observations and coordinating with the SMKN 2 Makassar school as a partner of this activity, followed by the socialization, monitoring and evaluation activities. The implementation method is a coaching approach method through socialization with discussion techniques (questions and answers) which are carried out offline using animated videos, presentation slides and relevant images related to road crossing and driving ethics and also safety driving’s tips on the road. This activity is expected to create positive attitudes and behaviors in orderly driving behavior on the road. The results obtained by the students have high enough motivation and are quite enthusiastic, so that the material presented is easy to understand.